12 The influence of microvascular obstruction on the relationship between remote zone extracellular volume and subsequent left ventricular volumes in survivors of ST-elevation myocardial infarction. (17th November 2015) - Carberry, J; Carrick, D; Haig, C; Rauhalammi, S; Ahmed, N; Mordi, I; McEntegart, M; Petrie, MC; Eteiba, H; Hood, S; Watkins, S; Lindsay, M; et al.
Abstract : Background: The clinical significance of extracellular volume (ECV) in remote myocardium post-STEMI has not been fully studied. Myocardial ECV can be estimated by cardiac magnetic resonance imaging (CMR). The aim of this study was to assess remote ECV and its changes over time in acute STEMI survivors. Methods: STEMI survivors were enrolled in a cohort study (BHF MR-MI – NCT02072850 ). CMR was performed at 1.5 Tesla (Siemens MAGNETOM Avanto) 2 days and 6 months post-MI. T1 MOLLI mapping was performed pre- and 15 min post-contrast (0.15 mmol/kg gadoterate meglumin). ECV was calculated as the difference in relaxation rate (R1 = 1/T1) for myocardium and left ventricular (LV) blood pool pre- vs. post-contrast, corrected for haematocrit (HCT). Associations were assessed between remote zone ECV and LV end-diastolic volume (LVEDV) as a measure of ventricular remodelling. Results: 140 patients (59 ± 11 years; 107 (76%) male) were enrolled. Remote ECV at baseline and follow-up was 22.4(3.0)% and 22.5(2.9)%, respectively (p = 0.644). At 6 months, LVEDV increased by 2(25) ml. Remote zone ECV was not associated with follow-up LVEDV or change in LVEDV. In a subgroup analysis, remote zone ECV at 2 days was associated with LVEDV at follow up in patients without CMR evidence of early microvascular obstruction (MVO) (–1.44 (–2.76, –0.12); p = 0.033; n = 53), but not those with MVO (n = 78). Similarly, remote zone ECV was associated with change in LVEDV in patients without MVO. Conclusion: In acute STEMI survivors, the presence of MVO is an influence on the relationship between remote zone ECV and left ventricular outcome.